Indian economy: Selected methodological advances - Mathew Joseph; Karan Singh; Ranjan Kumar Dash; Jyotirmoy Bhattacharya; Ritika Tewari (Indian Council for Research on International Economic Relations (ICRIER), 2011)
This paper develops tools to examine selected major issues in the Indian economy. The study computes the potential growth rate of the economy and the agricultural sector, extends the analysis of the fiscal stimulus and its effects, and estimates the short and long run elasticities of India's trade. This brings out the need for structural reforms in raising the potential growth rate of economy and that of agriculture to achieve a non-inflationary, high growth trajectory for the country. The fiscal stimulus effects indicate the importance of fiscal consolidation efforts to sustain high growth. The trade elasticities buttress the case for maintaining an appropriate real effective exchange rate.
Keywords: E 30; E 62; F 32; 330; Potential growth rate; Fiscal stimulus; Balance of payments; Exchange rate; Trade elasticities; Wirtschaftswachstum; Stabilisierungspolitik; Wirkungsanalyse; Indien